KISAH SHALEH A.S DAN TSAMUD DALAM AI-QUR’AN - Muhammad, Muhammad Thaib (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2019)
Shaleh a.s was a prophet and apostle sent by Allah Swt to the Tsamuds to preach and invite them to worship Allah and leave the worship of idols. Shaleh a.s are from the original Arab nation. He was Shaleh bin Ubaid ibn Aasif whose last lineage reached Sam bin Noah. Whereas the Tsamud according to Ibn Katsir they were a people descended from one of his grandfathers named Tsamud bin Amir. The Tsamud people lived in peace and enjoyed the blessings that Allah provided to them with gardens and springs and a variety of plants and many palm trees. And they chiseled mountains for them to become their castles or dwellings. They make idols as worship besides Allah Almighty. Therefore Allah sent the prophet Shaleh a.s as their apostle. But they don't want to believe him. They even gave Shaleh a miracle. When God brought a female camel, she always gave her milk to drink. However, they tried to kill him as a way of rejecting the preaching and calling on Shaleh a.s to worship Allah. After they had killed the camels, God sent down a terrible disaster, which caused a great storm and rain, so that they all died with bodies lying in their houses.